2006
DOI: 10.1128/jb.188.7.2692-2700.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Intestinal Life Cycle of Bacillus subtilis and Close Relatives

Abstract: Bacillus subtilis is considered a soil organism for which endospore formation provides a means to ensure long-term survival in the environment. We have addressed here the question of what happens to a spore when ingested. Spores displaying on their surface a heterologous antigen, tetanus toxin fragment C (TTFC), were shown to generate anti-TTFC responses not to the antigen contained in the primary oral inoculum but to those displayed on spores that had germinated and then resporulated. We then used reverse tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
261
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 305 publications
(279 citation statements)
references
References 30 publications
14
261
1
3
Order By: Relevance
“…This principle finding agrees with studies conducted with a mouse model (6,25). However, in those studies, vegetative cells were detected only in the small intestines of mice dosed with spores.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…This principle finding agrees with studies conducted with a mouse model (6,25). However, in those studies, vegetative cells were detected only in the small intestines of mice dosed with spores.…”
supporting
confidence: 91%
“…Between 0.13% and 1.23% of the original spore dose was estimated to have been retained in the GI tract of each chick (Table 2). This finding is comparable with that from work conducted in mice (6,25) and supports the notion that B. subtilis is a transient member of the chick GI microflora, which does not colonize the GI tract. The remainder of the original spore dose may have been shed in feces or germinated in the GI environment and subsequently died due to unfavorable conditions.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…Previous studies have shown that some Bacillus species could germinate and grow in the GIT of humans and mice (Hoa et al, 2001;Tam et al, 2006;Hong et al, 2009a, b). Spores have the advantage over vegetative cells of being resistant to the low pH of the stomach, ensuring the delivery of high numbers to the GIT.…”
Section: Discussionmentioning
confidence: 99%